2020
DOI: 10.1038/s41438-020-00427-5
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid and prunasin, two candidate biomarkers for endodormancy release in almond flower buds identified by a nontargeted metabolomic study

Abstract: Temperate fruit trees belonging to Prunus species have the ability to suspend (induce dormancy) and resume growth periodically in response to environmental and seasonal conditions. Endodormancy release requires the long-term accumulation of chill. Upon accumulation of cultivar-specific chill requirements, plants enter the state of ecodormancy, which means the ability to grow has been restored, depending on the fulfilment of heat requirements. As many different metabolic pathways are implicated in endodormancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…The ROS detoxification system is crucial for fatty acid unsaturation during dormancy ( Norman et al, 1991 , Erez et al, 1997 , Gabay et al, 2019 ). The elevated levels of non-enzymatic antioxidants, e.g., glutathione and ascorbate, are closely associated with the endodormancy release in deciduous species, including apple, peach, and almond ( Wang and Faust, 1990 ; Siller-Cepeda et al, 1992 ; Guillamón et al, 2020 ). In the present study, it was observed that ET treatment did not alter the GSH metabolism ( Figures 2C – E ) but maintained high H 2 O 2 levels for an extended period during endodormancy which could have a negative effect on fatty acid unsaturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ROS detoxification system is crucial for fatty acid unsaturation during dormancy ( Norman et al, 1991 , Erez et al, 1997 , Gabay et al, 2019 ). The elevated levels of non-enzymatic antioxidants, e.g., glutathione and ascorbate, are closely associated with the endodormancy release in deciduous species, including apple, peach, and almond ( Wang and Faust, 1990 ; Siller-Cepeda et al, 1992 ; Guillamón et al, 2020 ). In the present study, it was observed that ET treatment did not alter the GSH metabolism ( Figures 2C – E ) but maintained high H 2 O 2 levels for an extended period during endodormancy which could have a negative effect on fatty acid unsaturation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the balance between ROS production and scavenging is crucial for efficient fatty acid unsaturation and subsequently dormancy release and bud break. Indeed, higher levels of glutathione and ascorbate, the key scavengers of ROS, were found to be closely associated with the dormancy release in deciduous species, including peach and almond ( Siller-Cepeda et al, 1992 ; Guillamón et al, 2020 ). The upregulation of the oxidation-reduction process during the endodormancy release and bud break has also been demonstrated in many other deciduous species ( Beauvieux et al, 2018 ; Yu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…2019 ). Even more recently, phenylpropanoid compounds as cinnamic, p-coumaric, caffeic and ferulic acid have been described in the release of endodormancy in almond flower buds ( Guillamón et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A suitable temperature is a necessary condition for the survival of organisms, but the adaptability of various organisms to changes in temperature differs considerably 1 . A significant difference between plants and other multicellular complex organisms is that plants live in a fixed state.…”
Section: Introductionmentioning
confidence: 99%